2020
DOI: 10.6000/2292-2598.2020.08.04.13
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Causal Inferences and Semantic Priming in People with Williams Syndrome: An fMRI Study

Abstract: This study aimed at examining the ability of causal inferences and semantic priming of people with Williams syndrome (WS). Previous studies pointed out that people with WS showed deviant sentence comprehension, given advantageous lexical semantics. This study investigated the impairment in connecting words in the semantic network by using neuroimaging techniques to reveal neurological deficits in the contextual integration of people with Williams syndrome. Four types of word pairs were presented: causal, categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Another study by Fidler et al [ 24 ] confirmed the enhanced intersubjectivity and emotional responsiveness of people with WS compared to a group with mixed etiologies (e.g., Down syndrome, Angelman’s syndrome), including negative and positive emotions in facial display and vocal production. This atypical processing of faces in individuals with WS could result from deficiencies in contextual integration, which have been shown in the verbal studies by Hsu et al [ 25 ], Hsu and Tzeng [ 26 ], and Hsu [ 20 , 27 ], as well as the nonverbal studies by Hsu [ 28 , 29 , 30 ], and Hsu and Chen [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Fidler et al [ 24 ] confirmed the enhanced intersubjectivity and emotional responsiveness of people with WS compared to a group with mixed etiologies (e.g., Down syndrome, Angelman’s syndrome), including negative and positive emotions in facial display and vocal production. This atypical processing of faces in individuals with WS could result from deficiencies in contextual integration, which have been shown in the verbal studies by Hsu et al [ 25 ], Hsu and Tzeng [ 26 ], and Hsu [ 20 , 27 ], as well as the nonverbal studies by Hsu [ 28 , 29 , 30 ], and Hsu and Chen [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the nonverbal studies, people with WS showed delayed performances in contextual integration via background pictures and target objects in their visual [ 29 ], auditory [ 30 ], and cross-modal [ 28 ] forms. Two other studies show that their neural processing of semantically related words and face processing were also atypical [ 25 , 31 ]. In this study, different emotion types were used as contextual primes and were coupled with different emotion types as contextual targets.…”
Section: Discussionmentioning
confidence: 99%
“…The age difference (i.e., 5.3 vs. 4) implies discrepancy in processing between computerized three-dimension animation and traditional two-dimensional images. The cause of the difference might be due to deficiency in integrating contextual information in people with WS (Hsu, Karmiloff-Smith, Tzeng, Chin, & Wang, 2007;Hsu & Karmiloff-Smith, 2008;Hsu, 2013aHsu, , 2013bHsu, , 2013cHsu, , 2014aHsu, , 2014bHsu, , 2016bHsu, , 2017bHsu, , 2020aHsu, , 2020bHsu, , 2023Hsu & Chen, 2014c;Hsu & Tzeng, 2011), difficulty in understanding task demands (Van Herwegen, Dimitriou, & Runblad, 2013), or superficial knowledge of lexical semantics (Hsu & Lv, 2023). This deficiency was evident in integrating word meaning into context during sentence processing (Hsu, 2013a(Hsu, , 2023, connecting words in a semantic organization (Hsu, 2017b(Hsu, , 2020a, delayed performances on causal inference through comprehension of ambiguous words (Hsu, 2013a), deviant contextual integration using pictures (Hsu, 2013c), and deviant integration of propositions in people with WS (Hsu & Tzeng, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the difference might be due to deficiency in integrating contextual information in people with WS (Hsu, Karmiloff-Smith, Tzeng, Chin, & Wang, 2007;Hsu & Karmiloff-Smith, 2008;Hsu, 2013aHsu, , 2013bHsu, , 2013cHsu, , 2014aHsu, , 2014bHsu, , 2016bHsu, , 2017bHsu, , 2020aHsu, , 2020bHsu, , 2023Hsu & Chen, 2014c;Hsu & Tzeng, 2011), difficulty in understanding task demands (Van Herwegen, Dimitriou, & Runblad, 2013), or superficial knowledge of lexical semantics (Hsu & Lv, 2023). This deficiency was evident in integrating word meaning into context during sentence processing (Hsu, 2013a(Hsu, , 2023, connecting words in a semantic organization (Hsu, 2017b(Hsu, , 2020a, delayed performances on causal inference through comprehension of ambiguous words (Hsu, 2013a), deviant contextual integration using pictures (Hsu, 2013c), and deviant integration of propositions in people with WS (Hsu & Tzeng, 2011). Further atypical neurological information processing across verbal and nonverbal domains was reported in conceptual formation (Hsu, Karmiloff-Smith, Tzeng, Chin, & Wang, 2007), semantic priming (Hsu, 2017b), and face recognition (Hsu & Chen, 2014c;Mills, Alvarez, St George, Appelbaum, Bellugi, & Neville, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation